EFEKTIVITAS PASAL 152 (KHI) TENTANG PEMBERIAN NAFKAH IDDAH ISTRI CERAI TALAK DI DESA SORINOMO KECAMATAN PEKAT KABUPATEN DOMPU - Dwi Radha Putri Mentari (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2025)
This study is motivated by the researcher's attention to the implementation of article 152 KHI on iddah maintenance for divorced wives in Sorinomo village, Pekat sub-district, Dompu district. The problem is the non-implementation of Article 152 KHI on the provision of iddah maintenance for divorced wives, which results in legal uncertainty and can cause financial difficulties for ex-wives. In practice, the ex-husband does not provide iddah maintenance to the ex-wife because there is no sense of concern from the husband. This will result in legal uncertainty and can result in financial difficulties for ex-wives. The problem formulations in this study are: Firstly, How is the practice of providing iddah maintenance after divorce in Sorinomo Village, Pekat Sub-district, Dompu Regency? Secondly, How is the implementation of Article 152 KHI on the provision of iddah maintenance for divorced wives in Sorinomo Village, Pekat Sub-District, Dompu Regency. The type of method used is a qualitative method with an empirical approach. The data collection methods used are observation, interview and documentation. The results of the study show that: First, the practice of giving iddah maintenance after divorce in Sorinomo Village: limited resources, second, lack of knowledge and public awareness, third, cultural and traditional factors. Second, Implementation of Article 152 KHI regarding the provision of iddah maintenance for divorced wives in Sorinomo Village: lack of understanding, limited resources, lack of education from village institutions and KUA, cultural and traditional factors.